Amelioration of Ochratoxin A-induced immunotoxic effects by silymarin and vitamin E in White Leghorn cockerels. (March 2013) - Khatoon, Aisha; Zargham Khan, Muhammad; Khan, Ahrar; Saleemi, Muhammad Kashif; Javed, Ijaz
<x xml:space="preserve">Abstract</x> Silymarin (SL) is the bioactive extract of the plant Silybum marianum and Vitamin E (VE) is an important anti-oxidant. The present study was designed to evaluate potential ameliorative effects of SL and VE against Ochratoxin A (OTA)-induced immunotoxic effects in White Leghorn cockerels. One day-old birds were divided into 12 groups (20 birds/group) and fed basal diets amended with OTA (1.0 or 2.0 mg/kg) alone or in combination with SL (10 g/kg) and/or VE (200 mg/kg) for 42 days. Immunological in situ responses, including antibody formation against sheep red blood cells (7 and 14 days after both primary and booster injections), lymphoproliferative responses to avian tuberculin (30 days of age), and mononuclear phagocytic system function (i.e. by clearance of injected carbon particles) assay (42 days of age), were assessed. Results suggested that silymarin and Vitamin E alone or in combination ameliorated the immunotoxic effects induced by 1.0 mg OTA/kg but could not significantly impact on the effect from ingestion of 2.0 mg OTA/kg. The results of the present study suggested that both SL and VE possess an ability to ameliorate OTA-induced immunotoxicity in chicks. However, it remains to be determined whether/what SL:OTA or VE:OTA ratios are required to assure such mitigation of OTA-induced immunotoxicities.